2014
DOI: 10.1007/s10488-014-0576-y
|View full text |Cite
|
Sign up to set email alerts
|

A School-Based Post-Katrina Therapeutic Intervention

Abstract: The current study presents the implementation of a set of school based interventions in a greater New Orleans school district one year following Hurricane Katrina. The interventions included adaptation and implementation of evidence based treatments in a crisis situation with at-risk youth which involved training and clinical challenges. 386 students found to have significant depressive and/or disruptive disorder symptoms received treatment from the School Therapeutic Enhancement Program (STEP). Further, a dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 29 publications
2
4
0
Order By: Relevance
“…Given these results, our study suggests that stress-reduction interventions among hurricane-affected community members may be particularly useful if implemented at venues such as job fairs and forums on post-hurricane construction, in addition to more typical settings for post-disaster interventions such as mobile clinics in the immediate aftermath, as well as community mental health centers, faith-based organizations, and school settings. [40][41][42] The geographic distribution of the participants shown in Table 1 seems to support the fact that the present study covered a wide geographic area of Long Island, Queens, and Staten Island and involved area known to have had a wide variation in exposures to Sandy. The finding regarding younger age being significantly associated with greater perceived stress confirms previous literature suggesting that younger disaster victims suffer greater impairment than do older adults.…”
Section: Discussionsupporting
confidence: 77%
“…Given these results, our study suggests that stress-reduction interventions among hurricane-affected community members may be particularly useful if implemented at venues such as job fairs and forums on post-hurricane construction, in addition to more typical settings for post-disaster interventions such as mobile clinics in the immediate aftermath, as well as community mental health centers, faith-based organizations, and school settings. [40][41][42] The geographic distribution of the participants shown in Table 1 seems to support the fact that the present study covered a wide geographic area of Long Island, Queens, and Staten Island and involved area known to have had a wide variation in exposures to Sandy. The finding regarding younger age being significantly associated with greater perceived stress confirms previous literature suggesting that younger disaster victims suffer greater impairment than do older adults.…”
Section: Discussionsupporting
confidence: 77%
“…In the current study, we introduced a more concise, school-based post-disaster intervention system that integrated local personnel involved in high school education and mental health care prior to the earthquake. Goldman et al (2015) reported similar results, showing that depressive symptoms improved after intervention. These authors did not assess anxiety or PTSR; thus, we cannot further compare our intervention effects with those of the previous study.…”
Section: Feasibility Of School-based Interventionssupporting
confidence: 56%
“…Chemtob et al (2002) found reductions in reports of trauma-related symptoms in children following treatment, suggesting that interventions provided by therapists are effective. A previous report demonstrated the efficiency of a school-based postdisaster intervention system for youths called STEP (Goldman et al 2015). However, the STEP intervention requires considerable numbers of staff members and specialists as well as significant financial resources.…”
Section: Feasibility Of School-based Interventionsmentioning
confidence: 99%
See 1 more Smart Citation
“…As an alternative to propensity scores, matching can be made with existing predisaster behavioral screening scores available in school systems. For example, Goldman and colleagues (2015) studied the effects of school-based interventions for at-risk youth in a greater New Orleans school district 1 year following Hurricane Katrina. Students who had significant depressive and/or disruptive disorder symptoms received treatment using evidence-based interventions.…”
Section: Promising Avenues For Researchmentioning
confidence: 99%